Assessing the outcome of surgery for Dupuytren's disease of the hand - Rodrigues, Jeremy (2016)
Dupuytren’s disease (DD) is a fibroproliferative disorder causing deformity of fingers and disability. Different treatments exist ranging from dividing cords (needle aponeurotomy) through disease excision (fasciectomy) to disease excision with resurfacing with a skin graft (dermofasciectomy). A range of outcome measurements has been used in DD, including angular measurements of finger joints and patient-reported outcome measures (PROMs). This thesis hypothesised that the leading candidate outcome measures are inadequate (subject to bias, invalid, and/or uninterpretable) and that currently there is insufficient evidence to inform patient-centred treatment choice in DD. To investigate this, existing evidence was appraised and studies of validity and interpretability of outcomes were conducted. This comprised a systematic review and meta-analysis of surgical trials, a systematic review of interpretability of outcome measures, cross sectional studies of the validity of leading candidate outcome measures (joint angles, the Disabilities of the Arm, Shoulder and Hand tool (DASH), and the Unité Rhumatologique des Affections de la Main scale (URAM)), and a prospective cohort study of outcome interpretability and variables associated with functional outcome. Key findings: